Analisis Pemenuhan Kebutuhan Gender dalam Program Penataan dan Pembangunan Pasar Legi Surakarta - Shafa Diaz Nurina Putri; Tiyas Nur Haryani (Program Studi Ilmu Administrasi Negara Fakultas Ilmu Sosial dan Politik Universitas Sebela, 2022)
This study aims to analyze the fulfillment of practical and strategic gender needs in the structuring and development program of the Legi Market in Surakarta City. This research is included in the type of qualitative descriptive research. Sources of data used are primary and secondary data sources. Data was collected by using interview, observation, and documentation techniques. The selection of informants was determined using a purposive sampling method, with interview informants being the managers of Pasar Legi and users of Pasar Legi. Triangulation technique was used to test the validity of the data. Analysis of the data used is an interactive model analysis. The results showed that the practical needs of gender showed a dominant trait, from the 12 components studied there were 7 components that had been well met, namely the availability of toilets, clean water, breastfeeding rooms, health rooms, physical condition of market buildings, market security, and access to transportation. 2 other components, namely smoking rooms and child care facilities, are not yet available at Legi Market, and 3 other components, namely market cleanliness, availability of parking spaces, and information and communication technology facilities that still require improvement to meet the criteria properly. Meanwhile, gender strategic needs have not been in line with expectations, where gender responsive training is not available for managers and traders, training for traders has not reached all traders, and the implementation of gender responsive SOPs is not yet fully available.